DECISION SUPPORT SYSTEM FOR PROJECT SELECTION DEVELOPMENT USING TECHNIQUE FOR ORDER METHOD OF PREFERENCE BY SIMILARY TO IDEAL SOLUTION (TOPSIS) - Trisnadi, Deni (JATI (Jurnal Mahasiswa Teknik Informatika), 2018)
The construction project is a problem that has a certain period of time with allocation of limited resources, to carry out the tasks outlined. Infrastructure development plays an important role as one of the driving wheel of economic growth.The potential of construction services plays an important role in economic activities, particularly in infrastructure development activities. Selection of projects with potential for growth a company needs to consider and calculate based on a number of criteria.The advantages are due to the rapid development of infrastructure in Indonesia, especially in the regions East Java, CV. Bumi Langgeng Perdana Prima gets a lot of construction offerings. From the number of projects offered each has several criteria for determining the project which development will be done first. In deciding which project will be done CV. Bumi Langgeng Perdana Prima still uses its Own Calculation Results (OCR).With this done research and development Decision Support System (DSS) using the Technique for Order Preference method with similarity to Ideal Solution (TOPSIS) Can help CV. Bumi Langgeng Prime Prima in processing and analyzing existing data. In order to become a computerized decision-making system, so the process of determining development projects more precise and accurate.